DEVELOPMENT OF PHYSICS E-MODULES BASED ON KVISOFT FLIPBOOK MAKER APPLICATION ON CIRCULAR MOTION MATERIAL - Meylani, Evy (Journal of Learning and Technology in Physics, 2023)
This study aims to determine the level of feasibility, practicality and effectiveness of the physics e-module based on the Kvisoft Flipbook Maker application on Circular Motion material. The type of method used in this study is development or Research and Development (R&D) using the 4D model, but is limited to three stages: 1) define, 2) design and 3) develop. The research results based on the validation of material experts and media experts obtained a total score of 19.7, with an average of 4.92 and 16.78 with an average of 4.19 "very feasible" e-module to use. This validation was also carried out on physics teachers with an average of 4.22 and was declared "very feasible". For in the e-module practicality test based on student responses for small groups involving 5 students and the results of an average percentage score of 88.8% with the interpretation of "very practical". In the large group test involving 30 students and the results were 86% with the interpretation of "very practical". While the results of student learning tests through the pre-test and post-test given to 30 students consisting of 10 multiple choice questions, the learning outcomes of students' cognitive knowledge aspects were classified as effective because they had scores between (g) ≥ 0.70, namely 0 ,72. This shows that the e-module based on the kvisoft flipbook maker application on circular motion material is stated to be "very effective" and can improve student learning outcomes.Keywords: E-Module; Kvisoft Flipbook Maker; Circular Motion.